Behavior Change Management Model for Patients with Skin Diseases in Hospital-Based Dermatological Care: A Qualitative Educational Management Study - Shienty Gaspersz; Herry Sumual; Rolles N. Palilingan; Jeffry Sony Junus Lengkong (International Journal of Information Technology and Education, 2026)
This article presents a qualitative educational management study on the development of a behavior change management model for patients with skin diseases in hospital settings in Manado City. The study is grounded in the problem that clinical treatment for dermatological conditions is frequently not followed by consistent patient adherence to therapy, self-care routines, trigger avoidance, and long-term follow-up. The study employed a phenomenological qualitative design involving physicians, health professionals, and patients. Data were collected through in-depth interviews, focus group discussion, observation, and document analysis, and analyzed through data reduction, coding, thematic categorization, display, verification, and triangulation. The findings show that patient education has already been practiced as part of dermatological consultation; however, educational planning remains largely individual, implicit, situation-based, and dependent on each physician's experience. The implementation of education is mostly verbal, informative, and clinic-centered, while participatory dialogue, family involvement, written materials, follow-up documentation, and behavioral evaluation remain limited. Patients interpret behavior change as a gradual learning process involving cognitive understanding, emotional acceptance, confidence, professional support, and personal experience. The article proposes a contextual model consisting of needs-based planning, collaborative organization, participatory implementation, meaning reconstruction, reinforcement, and continuous evaluation. The model contributes to educational management by framing hospitals as non-formal learning spaces and patients as adult learners whose sustained behavioral change requires structured, empathetic, culturally sensitive, and continuously monitored education. The model also strengthens promotive and preventive functions in dermatological care by linking clinical management with patient learning and behavior change.